4 - Assessing China’s Relations with Africa - Besada, Hany (Africa Development, 2021)
China’s spectacular economic progress has led some security analysts and policy makers to question Beijing’s intentions in other parts of the world. This paper examines the extent to which China’s engagement with Africa has pro- duced mutual benefits for both and whether Africa is reaping the necessary benefits required for poverty alleviation and economic development. Chinese state-owned enterprises have invested billions of dollars in foreign reserves, construction, and engineering resources assisting African oil-producing export- ers. While many in the West have started to question China’s extraordinary level of interest in Africa – in particular, its economic engagement with per- ceived repressive regimes – African leaders view China’s entry as a means of pulling Africa onto the path of globalization. It is thus important that African leaders and policy makers ensure that Chinese trade and investment bring reciprocal and tangible be efits for Africans, and contribute to economic stability and good governance.